KAJIAN AGRIBISNIS KELAYAKAN PRODUK TELUR ASIN OMEGA 3 DI KABUPATEN HULU SUNGAI UTARA - Yan Yozef Agus Suratman (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
This study aims to determine technically the implementation in the business of making omega 3 salted eggs, to technically and economically determine the cost, income, and business feasibility of making omega 3 salted eggs in Sungai Pandan Hulu Village. Production process activities are carried out for 6 days starting from cleaning/selection of eggs to steaming and ready to be marketed. So there are 4 (four) production cycles. Using raw materials in the form of fresh duck eggs, while the auxiliary materials are coarse salt, ash/red brick powder, sufficient water, plus materials for steaming and packaging. The production capacity is 2,600 grains with a selling price of Rp. 3,200 / item. The total cost of production (TC) spent during the research period was Rp. 7,282,203.34. Total Revenue (TR) obtained during the research period is Rp. 8,320,000. The value of RCR (revenue cost ratio) is 1.1425. This means that RCR > 1, then the manufacture of omega 3 salted eggs in Sungai Pandan Hulu Village can be said to be profitable and feasible to cultivate